Intelligent Automation and Computer Engineering - Huang, Xu.; Ao, Sio-Iong.; Castillo, Oscar; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
A large international conference in Intelligent Automation and Computer Engineering was held in Hong Kong, March 18-20, 2009, under the auspices of the International MultiConference of Engineers and Computer Scientists (IMECS 2009). The IMECS is organized by the International Association of Engineers (IAENG). Intelligent Automation and Computer Engineering contains 37 revised and extended research articles written by prominent researchers participating in the conference. Topics covered include artificial intelligence, decision supporting systems, automated planning, automation systems, control engineering, systems identification, modelling and simulation, communication systems, signal processing, and industrial applications. Intelligent Automation and Computer Engineering offers the state of the art of tremendous advances in intelligent automation and computer engineering and also serves as an excellent reference text for researchers and graduate students, working on intelligent automation and computer engineering.
A Linguistic CMAC vs. a Linguistic Decision Tree for Decision Making -- A Multiple Criteria Group Decision Making Model with Entropy Weight in an Intuitionistic Fuzzy Environment -- Emergency HTN Planning -- Adaptive Ant Colony Optimization with Cranky Ants -- A Kind of Cascade Linguistic Attribute Hierarchies for the Two-Way Information Propagation and Its Optimisation -- Simulation Optimization of Practical Concurrent Service Systems -- A New Improved Fuzzy Possibilistic C-Means Algorithm Based on Weight Degree -- Low Cost 3D Face Scanning Based on Landmarks and Photogrammetry -- 3D Face Recognition and Compression -- Head Movement Quantification and Its Role in Facial Expression Study -- Enhanced Audio-Visual Recognition System over Internet Protocol -- Lossless Color Image Compression Using Tuned Degree-K Zerotree Wavelet Coding -- Motion Estimation Algorithm Using One-Bit-Transform with Smoothing and Preprocessing Technique -- Configuration of Adaptive Models in Arithmetic Coding for Video Compression with 3DSPIHT -- Ad Hoc In-Car Multimedia Framework -- Reliable Routing Protocol for Wireless Sensor Network -- 802.11 WLAN OWPT Measurement Algorithms and Simulations for Indoor Localization -- Residual Energy Based Clustering for Energy EfficientWireless Sensor Networks -- Fast Dissemination of Alarm Message Based on Multi-Channel Cut-through Rebroadcasting for Safe Driving -- Lightweight Clustering Scheme for Disaster Relief Wireless Sensor Networks -- On the Complexity of Some Map-Coloring Multi-player Games -- Methods to Hide Quantum Information -- Analyses of UWB-IR in Statistical Models for MIMO Optimal Designs -- Intruder Recognition Security System Using an Improved Recurrent Motion Image Framework -- Automatic Recognition of Sign Language Images -- Algorithm Using Expanded LZ Compression Scheme for Compressing Tree Structured Data -- Using Finite Automata Approach for Searching Approximate Seeds of Strings -- Speech Recognizer with Dynamic Alternative Path Search and Its Performance Evaluation -- Text Mining Decision Elements from Meeting Transcripts -- Double SVMSBagging: A Subsampling Approach to SVM Ensemble -- Clustering of Expressed Sequence Tag Using Global and Local Features: A Performance Study -- Research on Process Algebraic Analysis Tools for Electronic System Design -- Behavioural Hybrid Process Calculus for Modelling and Analysis of Hybrid and Electronic Systems -- Structured Robust Control for a Pmdc Motor Speed Controller Using Swarm Optimization and Mixed Sensitivity Approach -- Agents for User-Profiling, Information Filtering, and Information Monitoring -- Form-Based Requirement Definitions of Applications for a Sustainable Society -- A Dynamic Nursing Workflow Management System: A Thailand Hospital Scenario.
Keywords: Engineering; Software engineering; Electronics; Engineering; Computational Intelligence; Software Engineering/Programming and Operating Systems; Electronics and Microelectronics, Instrumentation